2016
DOI: 10.1021/acsenergylett.6b00415
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Photocatalytic Production of Hydrogen Peroxide from Water and Dioxygen with Bismuth Vanadate and a Cobalt(II) Chlorin Complex

Abstract: Efficient photocatalytic production of H2O2 as a promising solar fuel from H2O and O2 in water has been achieved by the combination of bismuth vanadate (BiVO4) as a durable photocatalyst with a narrow band gap for the water oxidation and a cobalt chlorin complex (CoII(Ch)) as a selective electrocatalyst for the two-electron reduction of O2 in a two-compartment photoelectrochemical cell separated by a Nafion membrane under simulated solar light illumination. The concentration of H2O2 produced in the reaction so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 65 publications
0
88
0
Order By: Relevance
“…[59][60][61] As discussed in the Introduction,a lmost all photoelectrochemical or photocatalytic H 2 O 2 productionsh ave generally been performedb yt he two-electron reduction of O 2 . [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] The development of ap hotoelectrochemicals ystem for producing H 2 O 2 with high current efficiency by using H 2 Oa nd O 2 as raw materials [ Figure 1(A) and (B), Eq. (8 a)] by at wo-photon process may be ap romisingt echnology from the viewpoint of practical applications.…”
Section: / Bivo 4 Photoanodementioning
confidence: 99%
See 2 more Smart Citations
“…[59][60][61] As discussed in the Introduction,a lmost all photoelectrochemical or photocatalytic H 2 O 2 productionsh ave generally been performedb yt he two-electron reduction of O 2 . [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] The development of ap hotoelectrochemicals ystem for producing H 2 O 2 with high current efficiency by using H 2 Oa nd O 2 as raw materials [ Figure 1(A) and (B), Eq. (8 a)] by at wo-photon process may be ap romisingt echnology from the viewpoint of practical applications.…”
Section: / Bivo 4 Photoanodementioning
confidence: 99%
“…Although little promisingt echnology for oxidativeH 2 O 2 productionf rom H 2 Oi sk nown, many studies investigating reductive H 2 O 2 production from O 2 have been reported. [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] These reactions have relied on the two-electron reduction of O 2 [Eq. (7)].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two‐electron oxygen reduction reaction (ORR) of dissolved oxygen (O 2 ) in water leads to formation of hydrogen peroxide (H 2 O 2 ) which is a versatile, high energy product, capable of participating in numerous further redox reactions and is an active species in a plethora of biological processes . Solar‐driven H 2 O 2 formation has been proposed for chemical energy storage . However, the widely used anthraquinone process for the formation of H 2 O 2 is known to be energy intensive .…”
Section: Figurementioning
confidence: 99%
“…[121] In this case, however,s eawater deactivated the photocatalyst, owing to the instability of BiVO 4 ,w hich started to dissolve in the presence of Cl À under solari llumination. [121] The (Figure 15). [116] The energy conversion efficiency of the H 2 O 2 fuel cell was evaluated as roughly5 0% by measurement of the output energy as electrical energy vs. consumed chemical energy of H 2 O 2 ,w hich is comparable to the efficiency of an H 2 fuel cell.…”
Section: Hydrogenfrom Black Sea Deep Watermentioning
confidence: 93%